Analisis keterampilan berfikir kreatif Fisika pada Peserta Didik Kelas XI IPA SMA Negeri 13 Halmahera Selatan - Muhtar, Ernawati (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2024)
This research aims to know the level of skill creative thinking physics at learnerss class XI IPA SMA Negeri 13 Halmahera Selatan. The kind of research is survey (ex post facto) that are descriptive to obtain quantitative data for research not giving treatment to respondents so that this research is only uncover and that it was without connect with to other variables. But the population or the research is all students class XI IPA SMA Negeri 13 Halmahera Selatan academic year 2015/2016 and sample selected conditions groups with the class in their entirety the class XI IPA SMA Negeri 13 Halmahera Selatan amounting to 32 students with 8 man and 24 woman becoming sample in this research. Research instruments used is the test skill creative thinking of physics have valid to be used. The result of the descriptive analysis indicate that skill mean score think is creative thinking physics learners class XI IPA SMA Negeri 13 Halmahera Selatan be over the category low with percentage 46,88%. As for the result of analysis to every indicator creative thinking physics show that the most prominent indicator is to find causes with mean score that is 2,70 and those the lowest indicator of guess is a result of an event with mean score that is 0,95 compared to the with other indicator. So that it can be concluded that level of skill creative thinking physics at learners/participant class XI IPA SMA Negeri 13 Halmahera Selatan still lower.